228k views
1 vote
Graph the image of A(1,3) after the described glide3) Translation: (x, y) = (x – 3, y+2)reflectionReflection: in x=2

Graph the image of A(1,3) after the described glide3) Translation: (x, y) = (x – 3, y-example-1

1 Answer

5 votes

Given the point A(1,3).

Translation:


(x,y)\rightarrow(x-3,y+2)=(1-3,3+2)=(-2,5)

This is:

And next, reflection in x = 2:

The image is point C(6,5).

Answer: (6,5)

Graph the image of A(1,3) after the described glide3) Translation: (x, y) = (x – 3, y-example-1
Graph the image of A(1,3) after the described glide3) Translation: (x, y) = (x – 3, y-example-2
User Islam Emam
by
5.0k points